Cover JGEET Vol 03 No 03 2018 - EDITOR, JGEET (Journal of Geoscience, Engineering, Environment, and Technology, 2018)
This Volume Consists of Research Article as follow: Analysis of Colombian Seismicity as a Way to Explain and Understand The Bucaramanga Nest Building of Turbiditic Gas Field Dynamic Model with a Simplified 3D Simulation Software Assessment of Microgravity Anomalies of Soil Structure for Geotechnical 2D Models The Morphotectono-Volcanic of Menoreh-Gajah-Ijo Volcanic Rock In Western Side of Yogyakarta-Indonesia 94 A Case Study Based Slope Stability Analysis at Chittagong City, Bangladesh Efforts on Geological Conservation to Watuadeg-Basalt Pillow Lavas at West Sumber, Berbah District, Sleman Regency, Yogyakarta Special Region-Indonesia